O paraíso na outra esquina, de Mario Vargas Llosa : espaços de sentido - Lima, Cássia Gianni de (2016)
This work aims at reading O paraíso na outra esquina, by Mario Vargas Llosa, focusing on the representation of space a category of narratives. Its main goal is to think of how space is presented and what is its functionality in the novel. For this, we understand space not only as a backdrop for the actions of the characters, but assuming decisive significance for the understanding of the entire work. Thus, the space becomes a functional element ever seen in its application and in relation to other elements. The first part of this work presents a recover of some theories which propose a conceptualization of literature, discuss the issue of representation, think the novel as a genre and, finally, consider questions about space as a term and in narrative. Among the approached studies are the ones of Eagleton (1997), Compagnon (2001) and Reis (2003), as well as those of Borneuf and Ouellet (1976), Bakhtin (1993; 2000) and Brandão (2007). The second chapter aims to give a brief resume of important events in the life of Mario Vargas Llosa as a writer and discuss the insertion of his literature in the Latin American context, as well as presenting the novel that will be analyzed in terms of its construction, theme, plot and critical receptivity. The third and final part, subdivided into another three, is the analysis of the multiple spaces contained in O paraíso na outra esquina. Initially, it focuses on the continental areas, Latin-America, Oceania and Europe, considering them in a center-periphery relationship and in their individual representation. Then it goes on to reflect on the internal and external spaces, while these are meaningful as an objective perspective and a possibility of living and learning, and those, as subjective perspective and spaces of memory, loneliness and self-discovery. Finally, we analyze the paradise while a slippery space of utopia, directly related to the individual concept that each character has of freedom and, therefore, with two different configurations.